Family Conflict Behind Childhood Depression: A Psychoanalytic Approach of the Main Character in Some Kind of Happiness by Claire Legrand - Anggita Galuh Dewayani; Sri Sumaryani (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This study explores how family conflict contributes to childhood depression through the portrayal of Finley's psychological structure in Claire Legrand's novel Some Kind of Happiness. Using Sigmund Freud's theory of personality—comprising the id, ego, and superego—this research examines how Finley's internal struggles reflect the emotional consequences of her parents' marital breakdown. Unlike previous studies, which have applied Freud's theory more broadly to symbolic or moral behaviour across multiple characters, this study offers a focused, in-depth psychoanalytic reading of a single child protagonist. Employing a qualitative descriptive method and a psychological approach, the analysis reveals that Finley's id expresses unconscious impulses driven by sadness and anxiety. At the same time, her ego serves as a mediator between these emotional needs and external expectations. Her superego, shaped by internalised family norms, imposes guilt and shame for emotional vulnerability. The conflict between these three components mirrors the tension within Finley's family and contributes to her emotional repression and depressive symptoms. This study highlights how literature can reflect the psychological impact of family dynamics on children, and how psychoanalytic theory offers valuable insights for understanding emotional trauma in young literary characters.